2022
DOI: 10.3390/jcm11030586
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Severe Vestibular Hypofunction after Systemic Gentamicin

Abstract: The importance of early evaluation by a neurotologist in patients with infective endocarditis treated with systemic gentamicin and its impact on the patients’ quality of life was evaluated. This is a longitudinal retrospective cohort study of 29 patients who received intravenous gentamicin for the treatment of infective endocarditis. Patients were classified into two groups: group A, before a neurotologist was included in the treatment protocol, and group B, after the inclusion of a neurotologist. The frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…First, Esteban-Sanchez and Martin-Sanz [ 13 ] have covered the topic of acute unilateral vestibulopathy in a rigorous and detailed study during a follow-up, trying to correlate measures of functional damage, postural deficiency, and disability to the clinical state of compensation, with clinical implications when vestibular rehabilitation is the treatment of choice. Induced bilateral vestibulopathy is the unwanted effect of some systemic medications, such as gentamicin; in their study, Ferreira-Cendón et al have shown how this effect could be reduced in patients with infectious endocarditis when an otoneurologist is included in the treating team to provide careful and continued measures of vestibular function to help in the continuation, or not, of gentamicin [ 14 ]. This probably could be expanded to other treatments with potentially ototoxic medications.…”
mentioning
confidence: 99%
“…First, Esteban-Sanchez and Martin-Sanz [ 13 ] have covered the topic of acute unilateral vestibulopathy in a rigorous and detailed study during a follow-up, trying to correlate measures of functional damage, postural deficiency, and disability to the clinical state of compensation, with clinical implications when vestibular rehabilitation is the treatment of choice. Induced bilateral vestibulopathy is the unwanted effect of some systemic medications, such as gentamicin; in their study, Ferreira-Cendón et al have shown how this effect could be reduced in patients with infectious endocarditis when an otoneurologist is included in the treating team to provide careful and continued measures of vestibular function to help in the continuation, or not, of gentamicin [ 14 ]. This probably could be expanded to other treatments with potentially ototoxic medications.…”
mentioning
confidence: 99%